MAN-MADE AND MILITARY EMERGENCY SITUATIONS - Yuldashev Elmirza Kholmirzayevich (Galaxy International Interdisciplinary Research Journal, 2022)
This article Accidents in gas treatment plants, biological and other treatment plants that cause pollution of the atmosphere, soil, groundwater and surface water with harmful substances in concentrations that pose a threat to people's health.